2007
DOI: 10.1017/s1740925x08000173
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Sox10 and Egr2 in myelin gene regulation

Abstract: Myelination in the PNS is accompanied by a large induction of the Myelin Protein Zero (Mpz) gene to produce the most abundant component in peripheral myelin. Analyses of knockout mice have shown that the EGR2/Krox20 and SOX10 transcription factors are required for Mpz expression. Our recent work has shown that the dominant EGR2 mutations associated with human peripheral neuropathies cause disruption of EGR2/SOX10 synergy at specific sites, including a conserved enhancer element in the first intron of the Mpz g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 50 publications
6
77
1
Order By: Relevance
“…Both sites are separated by 11 bp, and the distance between their centers corresponds exactly to two helical turns. This is closer than most previously identified composite binding elements for Sox10 and Krox20 (Jones et al, 2007). It also differs from previously identified sites in that it combines the Krox20 site with a monomeric rather than a dimeric Sox10 binding site.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Both sites are separated by 11 bp, and the distance between their centers corresponds exactly to two helical turns. This is closer than most previously identified composite binding elements for Sox10 and Krox20 (Jones et al, 2007). It also differs from previously identified sites in that it combines the Krox20 site with a monomeric rather than a dimeric Sox10 binding site.…”
Section: Discussioncontrasting
confidence: 46%
“…Sox10 activates the expression of peripheral myelin genes during terminal differentiation, including Mag, Mbp, Mpz, Pmp22, and Connexin 32 (Peirano et al, 2000;Bondurand et al, 2001;Jones et al, 2007. Sox10 is also directly involved in the activation of Krox20, which is a key activator of peripheral myelin genes (Ghislain and Charnay, 2006;Reiprich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An example is shown for the myelin-associated glycoprotein (Mag) gene (Fig. 5A), which was previously shown to have Egr2 and Sox10 binding within a conserved intronic region (39,40,42). These sites are flanked by H3K27ac, but the active histone mark is practically abolished at 3 days after nerve injury.…”
Section: In Vivo Analysis Of Enhancer Dynamics After Nerve Injury-mentioning
confidence: 96%
“…Our previous genomic analysis revealed that 5-10% of Egr2-and Sox10-binding sites colocalize (depending on spacing) in peripheral nerve (51), reflecting "composite elements" that have been identified in several myelin genes, including Gjb1, Pmp22, Mbp, Mag, and Mpz (11)(12)(13)(14)(15)(16)39). When sites of Egr2/Sox10 colocalization were examined in the context of active enhancer marks, the majority (73%) of the composite Egr2 and Sox10 peaks were marked with H3K27ac in the sham condition.…”
Section: In Vivo Analysis Of Enhancer Dynamics After Nerve Injury-mentioning
confidence: 99%
“…Furthermore, this region is recognized by an antibody against H3K27Ac (31), which marks active regulatory elements, and by an antibody against H3K4me3, indicative of an active promoter element ( Figure 4A). These findings led us to analyse this region for binding by EGR2/ KROX20, which is a transcription factor that works synergistically with SOX10 at adjacent binding sites to regulate gene expression during myelination (32,33). This did not reveal any evidence of EGR2/KROX20 binding within the alternative promoter or anywhere else at MTMR2 (data not shown).…”
Section: Sox10 Regulates Mtmr2-prom2 Activity In Schwann Cellsmentioning
confidence: 97%